A randomized controlled proof‐of‐concept trial of digoxin and furosemide in adults with cutaneous warts - Rijsbergen, M. (John Wiley and Sons Inc., 2019)

(untitled) (Br J Dermatol)
BACKGROUND: Topical ionic contraviral therapy (ICVT) with digoxin and furosemide inhibits the potassium influx on which DNA viruses rely for replication. Therefore, ICVT was hypothesized to be a potential novel treatment for cutaneous warts. OBJECTIVES: To assess the clinical efficacy, safety and tolerability of ICVT in adults with cutaneous warts. The secondary objective was to gain insight into the underlying working mechanism of ICVT. METHODS: Treatment with ICVT was assessed for efficacy, safety and tolerability in a single‐ centre, randomized, double‐blind, placebo‐controlled phase IIA trial. Eighty adult patients with at least two cutaneous warts (plantar or common) were randomized to one of four treatments: digoxin + furosemide (0·125%), digoxin (0·125%), furosemide (0·125%) or placebo. The gel was administered once daily for 42 consecutive days. Predefined statistical analysis was performed with a mixed‐model ancova. The trial was registered at ClinicalTrials.gov with number NCT02333643. RESULTS: Wart size and human papillomavirus (HPV) load reduction was achieved in all active treatment groups. A statistically significant reduction in wart diameter of all treated warts was shown in the digoxin + furosemide treatment group vs. placebo (−3·0 mm, 95% confidence interval −4·9 to −1·1, P = 0·002). There was a statistically significant reduction in the HPV load of all treated warts in the digoxin + furosemide group vs. placebo (−94%, 95% confidence interval −100 to −19, P = 0·03). With wart size reduction, histologically and immunohistochemically defined viral characteristics disappeared from partial and total responding warts. CONCLUSIONS: This study demonstrates the proof of concept for the efficacy of topical ICVT in adults with cutaneous warts.